Flow Cytometry in the Diagnosis of Canine B-Cell Lymphoma - Riondato, Fulvio; Comazzi, Stefano (Frontiers in Veterinary Science, 2021)
B cell lymphoma (BCL) is a heterogeneous group of lymphoid malignancies which comprise the majority of canine lymphomas. Diffuse large B cell lymphoma is the most common lymphoma subtype in dogs but other subtypes (e.g., marginal zone lymphoma, follicular lymphoma, mantle cell lymphoma, and others) have been described. This review aims to explore the use of flow cytometry to refine the diagnosis of canine BCL. Particular emphasis will be given to the possible identification of peculiar immunotypes, putative prognostic markers, staging and minimal residual disease.